Stavovi obiteljskih liječnika o profesionalnim bolestima - Ecimović Nemarnik, Renata (Array, 2019)
The aim of this study is to investigate the views of general practitioners regarding the reporting of occupational diseases and the possible link between work status, sickness and assessment of work ability with occupational diseases. The study also places focus on the need to improve collaboration with occupational medicine specialists, on general practitioners' need for education in certain areas of occupational health and occupational diseases, and on topics and ways of implementing education.The subjects were family physicians and general practitioners (50) employed in community health centers in Zagreb. The reported occupational diseases in family physician's surgeries were analyzed. It was found that 26% respondents reported occupational disease, 70% did not report it, and 4% did not know whether or not they had reported occupational disease in the last five years. The most commonly reported occupational diseases were diseases of the musculoskeletal system (38%) and skin diseases (38%). The reasons given for not reporting occupational diseases were that doctors were not aware that those were occupational diseases (91%), and because they feared that the patient may get fired (9%).The vast majority of respondents (94%) agreed that it is necessary to improve cooperation between family physicians and occupational medicine specialists. Seventy eight percent of family physicians were interested in education on how to recognize occupational diseases. Preventive team work on the part of occupational medicine specialists and family physicians using the 'check lists' in family physician's surgeries, and education courses on occupational health would improve primary prevention of occupational diseases, while early detection would halt the progress of occupational diseases and thus reduce ensuing disability caused by occupational disease.